Association between heavy metal exposure and heart failure incidence and mortality: insights from NHANES data (2003–2018) - Zebin Lin; Yongqi Dong; Xinlong Di; Yang Bai; Jianmin Tang; Guike Lai; Shengfang Wang; Xiaohu Wang; Yuhao Liu; Yipin Zhao (BMC Public Health)
Abstract Background Environmental heavy metal exposure is a potential yet understudied risk factor for heart failure (HF), a global health burden with rising prevalence. While toxic metals like cadmium (Cd), mercury (Hg), and arsenic (As) are linked to cardiovascular diseases, their roles in HF incidence and prognosis remain unclear. Methods The associations between heavy metals and HF outcomes were analyzed using NHANES 2003–2018 data (n = 11,592). Metals were measured in blood (Cd, Hg, Pb) and urine (As, Hg, others) using inductively coupled plasma mass spectrometry (ICP-MS). Confounding factors were addressed through propensity score matching (PSM). HF incidence was evaluated using logistic regression, while mortality was assessed via Cox regression. Mechanistic pathways were explored through causal mediation analysis. Results After PSM (n = 987, 337 HF cases), blood Cd showed a positive association with HF incidence (OR:1.35, 95%CI:1.05–1.72), while urinary Hg (OR:0.78, 95%CI:0.63–0.98) and As (OR:0.84, 95%CI:0.72–0.99) exhibited protective effects. Urinary As correlated with elevated cardiovascular mortality in HF patients (HR:1.19, 95%CI:1.04–1.35). Mediation analysis indicated Cd’s effect on HF was mediated via CHD/OMI, whereas Hg’s protection involved reduced CHD/OMI incidence. As directly lowered HF risk without mediation. Conclusion These findings underscore cadmium’s role as a risk factor and the paradoxical effects of mercury and arsenic: low to moderate concentrations of Hg/As may reduce HF risk through indirect pathways (e.g., reduced CHD/OMI for Hg) or direct cardioprotective mechanisms (for As), yet arsenic’s association with mortality highlights its long-term cardiovascular toxicity. Findings advocate for preventive strategies targeting metal exposure and further research integrating cumulative biomarkers.